Liver needle biopsy in children - Özsoylu, Şinasi; Koçak, Nurten; Gürsoy, Mustafa H. (The Turkish Journal of Pediatrics, 1980)
Percutaneous liver needle biopsies were carried out on 947 children with the age range of 3 hours to 17 years. Vim-Silverman needle was used mainly for the microscopic-examination of the organ. It is proved to be safe, easy and adequate method for the architectural examination of the liver.